Charming, influencing and seducing: a portrayal of everyday coaching. Issue 4 (4th May 2023) - Santos, Sofia; Jones, Robyn L.
ABSTRACT: Since a critical turn was embarked on two decades ago, research into sports coaching has increased in quality and quantity [see Jones, R. L. (2019). Studies in sports coaching . Cambridge Scholars Publishing]. Despite such welcome advances, the essence or heart of the activity remains contested terrain [Abraham, A., & Collins, D. (2011). Taking the next step: Ways forward for coaching science. Quest (grand Rapids, Mich), 63 (4), 366–385. https://doi.org/10.1080/00336297.2011.10483687; Jones, R. L., Edwards, C., & Tuim Viotto Filho, I. A. (2016). Activity theory, complexity and sports coaching: An epistemology for a discipline. Sport, Education and Society, 21 (2), 200–216. https://doi.org/10.1080/13573322.2014.895713]. Subsequently, the aim of this work was to inductively analyse the practice of a top-level sports coach to better understand the core of what he actually did whilst working. This was particularly in terms how he managed the working contexts and the others within it towards desired ends. In seeking a 'bottom up' construction of practice, the study adopted tenets from both grounded theory and phenomenological inquiry. More specifically, the fieldwork was conducted over a 6-month period at a top-level women's basketball club, with the data collection methods being ethnographic in nature, inclusive of participant observation and informal interviews. The main findings indicated that the coach in question, together with his coaching team, were engaged in a series of social, power-related, seductive strategies designed to charm athletes and others to 'buy into' the given agenda.